Potencial de alimentação de Chrysoperla externa (Hagen, 1861) (Neuroptera, Chrysopidae) em diferentes densidades de Uroleucon ambrosiae (Thomas, 1878) (Hemiptera, Aphididae) - Auad, Alexander M. [UNESP]; Freitas, Sérgio de [UNESP]; Barbosa, Leonardo R. [UNESP] (Sociedade Brasileira de Entomologia, 2003)
Feeding potential of Chrysoperla externa (Hagen) (Neuroptera, Chrysopidae) in different densities of Uroleucon ambrosiae (Thomas) (Hemiptera, Aphididae). The feeding potential of 2nd and 3rd instar larvae of Chrysoperla externa (Hagen, 1861) in relation to different densities of 30, 40 and 50 nymphs of Uroleucon ambrosiae (Thomas, 1878) at 3rd and 4th instars was evaluated. The treatments were individualized into 2.5 cm in diameter and 8.5 cm tall flat bottom glass vials and maintained in a controlled environmental chamber at 25±2 ºC temperature, 70±10% RH and 14 h photophase. A completely randomized experimental design with 10 replications was used. The consumption of the prey nymphs by the predator larvae was evaluated after 1, 2, 4, 8, 16 and 24 h from the beginning of the experiment and at every subsequent 24 h period until 2nd instar larvae molted or 3rd instar larvae pupated. Results have shown that for 2nd instar larvae, during the 1 h to 24 h period, there was a decreasing prey consumption at the 30 and 40 prey densities. However an increase in the consumption at the 50 prey density was observed. After this period, C. externa larvae presented a progressive increase on nymphs consumption as a function of the prey density. The same occurred with de 3rd instar predator larvae in all treatments. When daily mean consumption was evaluated the predator/prey ratio was 1:23, 1:27 and 1:33 for 2nd instar larvae and 1:27, 1:33 and 1:41 for 3rd instar larvae at 30, 40 and 50 nymph densities, respectively.
Keywords: Aphids; Biological control; Green lacewing; Predation